'All sunshine makes a desert'. Building interdisciplinary understanding of survival strategies of ancient communities in the arid Zerqa Triangle, Jordan Valley. (April 2019) - Kaptijn, Eva; Ertsen, Maurits W.
Abstract: Archaeological studies typically describe arid areas as extremely unpleasant areas for human occupation and use. Without suggesting that arid areas are pleasant places, however, this paper provides a reassessment of the meaning of aridity for an area showing a vast amount of evidence of (past) human activities. Several climatic proxy data suggest that at the transition between the late Bronze Age and the Early Iron Age (around c. 1300-1100 BC) the southern Levant witnessed more arid conditions, while after 1100 BC relatively moist conditions would have prevailed. In drylands, small changes in temperature and water availability can have large effects on subsistence options. Building on cooperation between an archaeologist and a water scholar, this paper offers an approach to study how people in the past were able to craft a livelihood in the arid environments in the southern Levant and elsewhere. Focusing on the Zerqa area, the paper explores the potential of this cooperation by studying effects of climatic changes at the transition from the Late Bronze Age to the Iron Age through a modelling approach. Changes in temperature and moisture availability were simulated, showing that increased aridity could have been met by either naturally available water (especially groundwater) or artificially added water (although the timing appears to be crucial). While the model approach under discussion offers an approximation of the past, it shows the potential impact of climatic changes on the subsistence of past communities. It shows that details can mean the difference between survival or collapse. Highlights: Modelling provides boundaries for thinking about ancient resilience. Rainfed crop yields could be sustained with irrigation, even in the frequent dry years. Increasing aridity might have been a trigger for expanding the irrigation system. The Zerqa Triangle was affected by the LBA crisis, yet continuity is visible as well. Aridity did not necessarily bring crisis, even in arid areas like the Zerqa Triangle.